PEMBERDAYAAN MASYARAKAT DESA BUAHAN KECAMATAN PAYANGAN – GIANYAR DALAM PENGELOLAAN POTENSI DESA - Negara, D.N.K.P.; Muku, I.D.M.K.; Nindhia, T.G.T. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana MengabdiDO - 10.24843/BUM.2018.v17.i01.p22, 2018)
Buahan Village is located in Payangan District, Gianyar Regency, Bali Province with 975 Ha area, divided into 5 sub villages namely Buahan, Gambih, Jaang, Satung and Susut. This village has a cool climate (temperature 180C - 280C), rainfall and springs are very supportive as agricultural, farms and plantations areas. For the potential development of the village, there are several conditions that need to be empowered / optimized such as: biogas potential, management of cattle manure and organic waste, livestock sanitation, early financial governance knowledge, organic and non-organic waste separation, early anticipation of drug abuse and healthy life behavior. Empowerment programs implemented include: Counseling and training of animal feed production from organic waste and making fertilizer from cattle manure with bio fermentation technology, maintenance training and utilization of biogas as an environmentally friendly energy source, counseling and implementation of cattle shedding healthy, financial education and literacy, education about danger of narcotics, psychotropic and additive substance, environmental sanitation and afforestation, making temple plan, socialization of organic and non-organic waste management. Implementation of these programs gained a very positive response and felt the benefits by the people of Buahan Village.